Зрительные стимулы в поведении стрекоз. I. Охота и посадка у стрекозы четырехпятнистой (Libellula quadrimaculata L.) - Мокрушов, П.А. (Вестник зоологии, 1972)
Visual stimuli causing hunting a prey and settling response in dragonflies were studied in field tests. Models of a prey were presented on a fishing-line. Dragonflies noticed white and black targets exceeding 5° in size against a contrasting background. Large targets and models composed of two little targets spaced by 10—20 mm were rejected. Even in the moment of seizure the angular diameter of a target usually was less than 5°. Dragonflies were offered for settling by sticks of different form and pattern. Light sticks oriented in the medial plane and light dots were preferred. The lines, which cross the base-line, skew lines, concurring parallel lines, light objects inhibited the settling response. The correspondence of the characters of optimal releasing stimuli to the detecting properties of certain visual interneurons is discussed. In receptive fields of these detectors mutual inhibition between excited sites of field is assumed.